Efficacy of toothbrushing procedures performed in intensive care units in reducing the risk of ventilator‐associated pneumonia: A systematic review (2019)
The aim of this systematic review (SR) was to assess whether toothbrushing‐based oral heath measure (OHM), performed in intensive care units, can reduce the risk of ventilator‐associated pneumonia (VAP). Dental biofilm removal has been considered important to prevent VAP. PUBMED, SCOPUS, WEB OF SCIENCE and Cochrane Central Register of Controlled Trials (CENTRAL) databases were searched up to and including December 2018 to identify randomized clinical trials (RCT) on the use of toothbrushing procedures in the prevention of VAP. Search was conducted by two independent reviewers. The risk of bias of each included study was assessed using the Cochrane Collaboration's domain‐based, two‐part tool. Random effects meta‐analyses were conducted thoroughly.Search strategy identified 215 potentially eli‐gible articles, of which 12 RCT were included. All studies evidenced the importance of OHM in mechanically ventilated patients in order to prevent VAP. Seven RCT (58.3%) found some degree of positive association between toothbrushing, alone or associated to oral topical chlorhexidine (CHX), and a potential reduction of mechani‐cal ventilation‐related outcomes and dental biofilm/oral bacteria. However, pooled estimates did not identify an additional decrease of VAP incidence for any of the tested procedures (ie, toothbrushing + CHX versus swab/gauze cleaning + CHX or toothbrushing + CHX versus toothbrushing alone or + placebo). Toothbrushing does not seem to promote a reduction of VAP‐outcomes compared to swab/gauze clean‐ing, when topic CHX is applied for oral hygiene of patients submitted to mechanical ventilation